Penerapan Metode Agile Untuk Membangun Sistem Informasi Monitoring Santri Pondok Modern Asy-Syifa Balikpapan - Sayid Esa Tri Buana; Lovinta Happy Atrinawati; M. Gilvy Langgawan Putra (Ikatan Ahli Informatika Indonesia, 2021)
Pondok Modern Asy-Syifa Balikpapan is one of the organizations engaged in education based on Islamic boarding education that is independent, private and legally incorporated. Apart from its private status, it does not make the achievement and application of student discipline lagging behind other educational institutions. The problems that occur are the processing of achievement data, violations and permits which are still done manually and do not use automatic data storage (databases), as well as the need for monitoring of achievements, violations and permits carried out by students to determine the level of student activity. Sistem Informasi Monitoring Santri (SIMS) is an application developed as a solution to these problems. SIMS was developed using the agile software development method with the scrum model which has stages in the form of sprint planning, daily scrum, sprint review and sprint retrospective. Laravel framework is used for system development by applying the concept of model, view and controller (MVC). There are 36 product backlogs carried out in 6 sprints with the main features to manage student data, achievements, violations, permits, and monitor students. It is hoped that the SIMS can assist in recording and monitoring student achievements, violations and licensing at Pondok Modern Asy-Syifa Balikpapan.